Indefinite quantifiers and their teaching to foreign speakers (Ogigia. Revista Electrónica de Estudios Hispánicos, 2019)
This article proposes a new approach to the teaching of indefinite quantifiers. The problems identified in the study of these lexical items in normative grammars have decisively affected the treatment of these units by texts of Spanish as a foreign language, all of which requires a reassessment of the subject from a didactic perspective in order to improve the teaching of indefinite quantifiers to foreign students.
Keywords: Indefinite quantifiers; Spanish as a foreign language; Normative grammars; Texts of Spanish as a foreign language; Didactic